First record of darter goby, Ctenogobius boleosoma (Jordan & Gilbert, 1882) (Gobiiformes: Gobiidae), in the Mediterranean with notes on larval morphology and cryptic diversity - MAVRUK, SINAN; TOSLAK, CIHAN; YALIM, F. BANU; ÜTÜK, ARMAĞAN ERDEM; KARA, ALPASLAN; AKTAŞ, ÖZGÜR; YÜKSEK, AHSEN (Mediterranean Marine Science, 2022)
Darter goby, Ctenogobius boleosoma (Jordan & Gilbert, 1882), is a small euryhaline fish of the Gobiidae family (Gobiiformes). It is naturally found in the shallow marine and brackish waters of the Western Central Atlantic. This study reports the first record of C. boleosoma in the Mediterranean Sea. In August and October 2019, two postflexion stage larvae were sampled during ichthyoplankton surveys in Antalya Bay in the Northeastern Mediterranean. The larvae were identified using the barcoding of cytochrome oxidase 1 gene sequence of mitochondrial DNA (COI). The morphology of the pre-transitional stage larvae was described and compared to previously published data. A phylogenetic analysis revealed that two distinct clades of C. boleosoma exist in its distribution range. The COI records belonging to one of the clades were generally collected within the Caribbean Sea, while the others were collected primarily in North American Western Atlantic waters from Florida to North Carolina. The average divergence between the clades was calculated to be 9.36 ± 1.34 (± 95% confidence interval), which likely indicates the existence of undescribed species. The specimen from the Mediterranean was identified as most closely related to the North American clade. This study shows how the integrative taxonomy of ichthyoplankton can improve knowledge about non-indigenous fish in the Mediterranean.